2013
DOI: 10.1016/j.atherosclerosis.2013.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ileal apical but not basolateral bile acid transport reduces atherosclerosis in apoE−/− mice

Abstract: Objective Interruption of the enterohepatic circulation of bile acids induces hepatic bile acid synthesis, increases hepatic cholesterol demand, and increases clearance of apoB-containing lipoproteins in plasma. Based on these effects, bile acid sequestrants have been used for many years to treat hypercholesterolemia and the associated atherosclerosis. The objective of this study was to determine the effect of blocking ileal apical versus basolateral membrane bile acid transport on the development of hyperchol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Our observation that RSV does not affect OSTα protein expression has physiological significance. Lan et al [41] showed recently that inhibition of ASBT, but not OSTα, is required to achieve plasma cholesterol reduction when blocking intestinal bile acid reabsorption. NTCP degradation has been shown previously to occur via the ubiquitin-proteasome pathway [42].…”
Section: Discussionmentioning
confidence: 98%
“…Our observation that RSV does not affect OSTα protein expression has physiological significance. Lan et al [41] showed recently that inhibition of ASBT, but not OSTα, is required to achieve plasma cholesterol reduction when blocking intestinal bile acid reabsorption. NTCP degradation has been shown previously to occur via the ubiquitin-proteasome pathway [42].…”
Section: Discussionmentioning
confidence: 98%
“…The effect of inactivation of the Asbt on development of hypercholesterolemia and atherosclerosis in female LDLr and apoE null mice maintained for 16 weeks on an atherogenic diet has been reported recently [29]. In that study, introducing the Asbt null allele into the LDLr null or apoE null backgrounds resulted in significant reductions in total plasma cholesterol, apoB-containing lipoprotein (VLDL plus LDL) cholesterol, and the plasma cholesterol exposure (area under the curve) over the 16-week dietary challenge.…”
Section: Effect Of Blocking Ileal Apical Brush Border Membrane Bile Amentioning
confidence: 99%
“…In agreement with the proposed role of the FXR-FGF15 pathway as a negative regulator of hepatic bile acid synthesis, there was a strong inverse correlation between the levels of mRNA expression for ileal FGF15 and hepatic Cyp7a1 in these models. However even more intriguing, there was a strong direct correlation between ileal FGF15 mRNA expression and total plasma cholesterol levels, and between ileal FGF15 mRNA expression and aortic cholesterol content, a measure of atherosclerosis [29]. The question of whether a similar relationship exists between plasma levels of FGF19 (human ortholog of mouse FGF15) and markers of atherosclerosis exists in humans has not yet been examined.…”
Section: Effect Of Blocking Ileal Apical Brush Border Membrane Bile Amentioning
confidence: 99%
“…More recently, Lan et al showed that mice lacking the intestine basolateral bile acid efflux transporter ostα had significantly reduced bile acid pool size but also lower hepatic CYP7A1 gene expression (10), which was resulted from bile acid retention in the intestine that leads to FGF15 induction. The same group also demonstrated that mice lacking the intestine apical sodium dependent bile acid transporter (ASBT) showed reduced intestine FGF15 expression, higher hepatic CYP7A1 expression and resistance to atherosclerosis development (11). These studies reiterated the importance of gut-liver signaling axis in the regulation of bile acid and lipid homeostasis.…”
Section: Introductionmentioning
confidence: 99%